EFFECTIVENESS OF VACCINATION AGAINST HUMAN PAPILOMA VIRUS - Rojas Cisneros, Noemí (2019)
The human papillomavirus (HPV) has a high prevalence in young women, which is why it is considered a public health problem. As their main form of transmission is sexual relations, it is estimated that around 80% of individuals will have contact with this virus in the course of their lives. According  to  reports  from  the  World  Health  Organization  (WHO),  the  human  papillomavirus  (HPV) associated with cervical cancer, ranks fourth among the most common types of cancer that affect women, with an estimated number of 570,000 deaths in 2018. In addition, WHO includes the HPV vaccine as part of national vaccination programs based on the following considerations: It  constitutes  a  public  health  priority;  the  introduction  of  these  vaccines  is  feasible  from a  programmatic  point  of  view;  sustainable  financing  can  be guaranteed;  It  has  cost-effectiveness  as  a vaccination  strategy;  and  focuses  on  teenage  girls  before  the  start  of  active  sex  life;  taking  into  account the aforementioned, it should be considered that the target population will primarily be made up of girls between the ages of 9 or 10   up to 13 years old.